Embodied Austerity: Narratives of Early Austerity from a Homelessness and Resettlement Service. Issue 1 (2nd January 2018) - Daly, Angela
ABSTRACT: The impact of austerity and welfare reform on staff in the caring services is an emerging story yet to be fully told. This paper presents three narratives of early austerity drawn from 14 in-depth interviews with staff of a small homelessness and resettlement service in England from 2011 to 2014. Experiences are represented through narratives of 'emerging realities', 'deletion' and 'changing relations'. The workers' stories revealed that the extent of welfare reforms and funding cuts not only impacted on the provision of services, but also on personal and professional values held by homelessness and resettlement service staff. Ethics of care, as embodied ethical practice in emotional, identity and interactive work, formed the basis for relationships between staff and homeless people or those at risk of homelessness. The rapidly changed funding and policy context for homelessness and resettlement services destabilised workers' self-concept as providers of relational care. A notion of 'embodied austerity' emerged from staff reflections on everyday experiences of austerity over time and contributes, perhaps, to a common story of workers' experiences during a period of social welfare in hard times.